The Relationship between Hypertension and Periodontitis: A Cross-Sectional Study - Rosa, Rossana Abud Cabrera [UNESP]; Rodrigues, João Victor Soares [UNESP]; Cláudio, Marina Module [UNESP]; Franciscon, João Paulo Soares [UNESP]; Mulinari-Santos, Gabriel [UNESP]; Cirelli, Thamiris; de Molon, Rafael Scaf [UNESP]; Gouveia Garcia, Valdir; Theodoro, Leticia Helena [UNESP] (MDPI, 2023)
Recent evidence suggests an association between hypertension and periodontitis, although the pathways and implications underlying both chronic conditions are still poorly understood. Therefore, the aim of this study was to evaluate the relationship between hypertension and periodontitis through an observational clinical study using periodontal, physical, and biochemical analyses in hypertensive and non-hypertensive individuals with periodontitis. A total of one hundred patients were divided into two groups. The first group was hypertensive patients with periodontitis. The second group was non-hypertensive patients with periodontitis. Periodontal parameters of probing depth, bleeding on probing, and clinical attachment level were evaluated. The systolic, diastolic, mean, and differential blood pressure were measured in the physical examination. In addition, body mass index and waist–hip ratio were verified. Biochemical tests for glycated hemoglobin, fasting blood glucose, estimated blood glucose, total cholesterol, high-density lipoprotein, creatinine, glutamate pyruvate transaminase, glutamic oxaloacetic transaminase, and C-reactive protein were evaluated. The data were submitted for statistical analysis (α = 0.05%). The results of this study demonstrated that patients with cardiovascular disease did not present with worse periodontal clinical parameters in the conditions studied. However, it is important to bear in mind that this cross-sectional study has some inherent limitations to its design; therefore, to study the relationship between hypertension and periodontitis further, an interventional randomized clinical trial should be conducted.
Keywords: hypertension; inflammation; observational study; periodontitis